THE ROLE OF FEMALE HADITH NARRATORS: Tracing the Degeneration of Gender Roles in Hadith Narration - Rukmana, Fachruli Isra; Najiyah, Nur Laili Nabilah Nazahah; Putri, Recha Tamara; Akmaluddin, Muhammad (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
Patriarchal domination has marginalized women’s roles in narrating hadith and contributing to Islamic knowledge, portraying them as incomplete beings deprived of rights and a voice. This study addresses three questions: a) What were women’s contributions to hadith narration? b) Who were the notable female hadith narrators from the era of the Companions to the atbāʾ al-tābiʿīn? c) Why is it essential to redefine gender roles in hadith narration? Using a qualitative, library-based approach, this research relies on al-Kutub al-Tisʿah as the primary source, supplemented by books, articles, journals, and websites. Data analysis involves condensation, presentation, and conclusion. Findings reveal women’s significant contributions to hadith transmission during the early Islamic period, especially among the sahabah, with figures like Umm Salamah and ‘Amrah bint ‘Abd al-Raḥmān ibn Sa’ad. However, this role declined in later generations due to wars, restrictive political policies during the Umayyad era, and cultural norms limiting women’s participation in education, politics, and Islamic scholarship. Additionally, the expansion of Islamic governance and the internalization of patriarchal values further hindered female involvement in Islamic propagation. This study underscores the need to revisit and empower women’s roles in hadith narration to restore their rightful place in Islamic intellectual history. [Dominasi patriarki telah meminggirkan peran perempuan dalam periwayatan hadis dan kontribusi mereka terhadap pengetahuan Islam, menggambarkan mereka sebagai makhluk yang tidak utuh, tanpa hak dan suara yang layak. Penelitian ini membahas tiga pertanyaan utama: a) Apa kontribusi perempuan dalam periwayatan hadis? b) Siapa saja periwayat hadis perempuan yang menonjol dari masa sahabat hingga atba' al-tabi'in? c) Mengapa penting untuk mendefinisikan ulang peran gender dalam periwayatan hadis? Dengan menggunakan pendekatan kualitatif berbasis studi pustaka, penelitian ini mengandalkan al-Kutub al-Tis’ah sebagai sumber utama, didukung oleh buku, artikel, jurnal, dan situs web. Analisis data dilakukan melalui proses kondensasi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan kontribusi perempuan yang signifikan dalam transmisi hadis pada masa awal Islam, khususnya di kalangan sahabat, dengan tokoh-tokoh seperti Umm Salamah dan ʿAmrah bint ʿAbd al-Raḥmān ibn Saʿad. Namun, peran ini mengalami penurunan pada generasi berikutnya akibat perang, kebijakan politik yang membatasi pada era Dinasti Umayyah, dan norma budaya yang membatasi partisipasi perempuan dalam pendidikan, politik, dan keilmuan Islam. Selain itu, perluasan pemerintahan Islam dan internalisasi nilai-nilai patriarki semakin menghambat keterlibatan perempuan dalam dakwah Islam. Penelitian ini menekankan pentingnya meninjau kembali dan memberdayakan peran perempuan dalam periwayatan hadis untuk mengembalikan posisi mereka yang seharusnya dalam sejarah intelektual Islam.]